GARBAGE FOR PROJECT BASED LEARNING MEDIA TO FORM PANCASILA STUDENT PROFILES IN MADRASAH IBTIDAIYAH - Ida Farihatul Maria; Suwardi Suwardi; Peni Susapti (STAI Ma'had Aly Al-Hikam Malang, 2025)
Garbage disrupted the sustainability of nature and human health, so it needs to be addressed by recycling garbage into learning media. This study aims to find the steps of Project Based Learning (PjBL) model using garbage, as well as to test its influence on the formation of Pancasila Student Profile in Madrasah Ibtidaiyah. The study uses a quantitative approach of True Experiment type. The population and sample of this study were students of Madrasah Ibtidaiyah in Tuntang District, Semarang Regency. Data collection using questionnaire, interview, observation methods. Data analysis using the Shapiro Wilk formula, F-test, t-test, and Gainscore. The results of the study found nine steps in PjBL model by garbage, namely; 1) student conditioning; 2) delivery of learning objectives; 3) asking essential questions; 4) project explanation; 5) making and monitoring project; 6) presentation of results; 7) reflection; 8) drawing conclusions; 9) evaluation. This study also proves that Project Based Learning model has a significant influence on the formation of Pancasila Student Profile and can increase the formation of Pancasila Student Profile character by 17.4%. Theoretically, the results of this study have contributed to developing the PjBL learning model, both in terms of developing steps and learning media. Keywords: Project Based Learning; Garbage; Pancasila Student Profile